Level of anxiety versus self-care in the preoperative and postoperative periods of total laryngectomy patients - Clara Inés Flórez Almonacid; Alfredo Jurado Ramos; María-Aurora Rod
Abstract Objective: estimate the prevalence of anxiety in laryngectomy patients in the pre and postoperative periods and its relation with the self-care level. Method: observational research of 40 patients with stage IV laryngeal cancer. Three observations took place: in the preoperative phase, at seven and at 14 days after the surgery; between June 2010 and December 2012. Two self-care levels were defined: self-sufficient and needing help for activities of daily living and treatment-related activities. To assess the anxiety levels, Zigmond's hospital anxiety scale (1983) was used. Results: in the preoperative and postoperative phases, the patients presented high levels of anxiety. Concerning self-care, on average, self-sufficient patients presented lower levels of anxiety than patients who needed help to accomplish activities of daily living and activities deriving from the surgery, without significant differences. Conclusion: anxiety is present at all times in laryngectomy patients and the reduction of the self-care deficit seems to decrease it, without putting a permanent end to it.